2008
DOI: 10.1080/09593980701588284
|View full text |Cite
|
Sign up to set email alerts
|

Clinometric properties of the six-minute walk test in individuals undergoing rehabilitation poststroke

Abstract: The 6-minute walk test (6MWT) is commonly used to measure walking ability. The purpose of this study was to determine the test-retest reliability and concurrent and construct validity of the 6MWT in patients who were actively undergoing inpatient rehabilitation poststroke. Thirty-seven patients undergoing inpatient rehabilitation after a stroke participated; mean age was 66.3 years and mean time since stroke was 33.7 days. Patients underwent two 6MWT trials with 1-3 days between trials. Additional outcome meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
123
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(128 citation statements)
references
References 44 publications
0
123
0
5
Order By: Relevance
“…The participant demonstrated improvement on all motor outcomes and all but one nonmotor outcome at EOT and maintained or improved at EOT14 (Tables 2 and 3). Tables 2 and 3 also display minimal clinically important difference (MCID) and minimal detectable change (MDC; Fulk et al, 2008;Lang, Edwards, Birkenmeier, & Dromerick, 2008;Lin et al, 2009;Page, Fulk, & Boyne, 2012). The participant demonstrated a 20-point improvement on the FMA at EOT, achieving the MCID and MDC at EOT and EOT14.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participant demonstrated improvement on all motor outcomes and all but one nonmotor outcome at EOT and maintained or improved at EOT14 (Tables 2 and 3). Tables 2 and 3 also display minimal clinically important difference (MCID) and minimal detectable change (MDC; Fulk et al, 2008;Lang, Edwards, Birkenmeier, & Dromerick, 2008;Lin et al, 2009;Page, Fulk, & Boyne, 2012). The participant demonstrated a 20-point improvement on the FMA at EOT, achieving the MCID and MDC at EOT and EOT14.…”
Section: Resultsmentioning
confidence: 99%
“…Nonmotor function was assessed using the Center for Epidemiologic Studies Depression Scale (Shinar et al, 1986), the Stroke Impact Scale (SIS; Duncan et al, 1999), and the Trail Making Test Parts A and B (Tamez et al, 2011). Outcomes for cardiopulmonary function were a CPX test and the Six-Minute Walk Test (6MWT; Fulk, Echternach, Nof, & O'Sullivan, 2008). Motor and nonmotor outcomes are described in detail in the online supplemental materials (available at http://ajot.aotapress.net; navigate to this article, and click on "Supplemental Materials").…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, our objectives were to investigate (1) crosssectional convergent construct validity of the ABC scale; (2) known-groups validity (between fallers and non-fallers, and by gender and mobility status); (3) test-retest reliability of the ABC scale; and (4) internal consistency. Based on earlier studies, 9,15 our hypothesis was that correlations would be moderate between scores on the ABC scale and the TUG test, 16 the 10TW, 17 the 6MWT, 18,19 and subjective physical health status measured by the SF-36 physical component summary score. 20,21 …”
Section: Ré Sumémentioning
confidence: 99%
“…The study by Blennerhassett & Dite (2004), which was conducted in the sub-acute phase after stroke, showed the largest absolute improvement, with a difference of 116m between the intervention and the control group. This difference is greater than the 13% change which has been reported as the minimum clinically relevant change (Flansbjer et al, 2005;Fulk et al, 2008). Three more studies also showed clinically relevant changes (Salbach et al, 2004;Pang et al, 2005;Mudge et al, 2009).…”
Section: Walking Distancementioning
confidence: 65%